Direktorat Jenderal Kekayaan Intelektual sebagai Turut Tergugat dalam Perkara Gugatan Penghapusan Merek Terdaftar (Studi Putusan Nomor 991 K/Pdt.Sus-HKI/2019) - Jerry Pratama (TERAJU: Jurnal Syariah dan Hukum, 2022)
Trademark is ones of intellectual property protected by the Directorate General of Ministry of Law and Human Rights based on the First to File principle. In principle, the registered trademark must be used by the applicant for goods and/or services. The trademark that has not been used for 3 years implied that the third person can file a lawsuit regarding the deletion of the trademark to the Commercial Court. The lawsuit will involve interested parties, such as the Trademark Applicant as a defendant and Directorate General of Intellectual Property as a co-defendant. The research wants to describe how the Directorate General of Intellectual Property protects trademark as one of intellectual property and how important to involve the Directorate General of Intellectual Property Ministry of Law and Human Rights as a co-defendant on the lawsuit. The researcher took the research object based on verdict number 991 K/Pdt.Sus-HKI/2019 in the case of trademark deletion where Directorate General of Intellectual Property didn't involve as a co-defendant on the lawsuit. The result of this research shows that there is no obligation to involve the Directorate General of Intellectual Property as a co-defendant in the case of the trademark deletion lawsuit.